Intracellular pH in human skeletal muscle by 1H NMR. - Pan, J W (1988)
We report here the in vivo observation of the imidazole protons (C-2 and C-4) of carnosine (beta-Ala-His) by 1H NMR at 4.7 T in human skeletal muscle. The relationship between the pH and chemical shift of the C-2 and C-4 resonances was determined analytically. These titration curves were used to measure the resting pH of human muscle in vivo, 7.01 x 0.04 (C-2 proton) and 6.97 +/- 0.10 (C-4 proton). An in vivo titration curve of the C-2 proton resonance was determined by interleaving 1H and 31P NMR spectra after exhaustive exercise, during which muscle pH recovers from an acidic value of 6.1. We observed excellent agreement between the pH values as determined by the C-2 resonance of carnosine and that of inorganic phosphate. Carnosine provides an excellent pH indicator since (i) its concentration is relatively stable and (ii) it allows measurement of proton metabolites and pH to be achieved through the same coil, thus enabling a better signal/noise ratio and better localization.